POTENSI CADANGAN MINERAL DAN BATUBARA DI INDONESIA DAN DUNIA - Arif Setiawan (INTAN Jurnal Penelitian Tambang, 2018)
Mineral and coal resources and reserves in the world even in Indonesia need to be known, considering that until now more and more industries need it, so that it can cause a reduction in raw material supply for the industry. To find out the amount of resources and reserves, data or information is needed, so after knowing the relevant information, it is expected to know what strategies to do. The method used is the comparison between Indonesian data and world data so that the percentage of ownership in Indonesia can be known. The results showed that coal in Indonesia was estimated to range from 2% -3% of coal in the world. For metal minerals, Indonesia had 6.08% nickel, 6.82% cobalt, 14.05 lead, 9.63% zinc, 3.33% bauxite, 0.72 iron, 4.63 gold, 16.67% tin , 3.29% copper, 19.17 manganese, 0.44% chromium, 0.17 titanium.